Change, conflict and sense of place : a case study of the inshore fishing community in the Victoria and Alfred Waterfront - Kilian, Darryll (Department of Environmental and Geographical Science, 2024)
The revaluation of place in geographical discourse has bolstered research which highlights both the global and local significance of places. Waterfront places have, as a result of their revitalisation, become the locus where capital and community intersect. The redevelopment of Cape Town's Victoria and Alfred Docks offers unique insights into understanding spatial change, conflict and sense of place. Like its international precedents, the evolution, decline and redundancy of the Victoria and Alfred Waterfront (V &AW) is a direct outcome of the wider processes of capital accumulation and technological transformation. Conflictual relations between the V &AW developers and planners and the Fishing Industry over the appropriate utilisation of dockland space, together with current spatial and functional restructurings, have negatively impacted upon the inshore fishing community working and living in the dockland. Ongoing commodification of this dockland area has directly contributed to feelings of uprootedness among the inshore fishermen, a community whose sense(s) of place and social and cultural identities are inextricably tied up with their past and present daily existence in the Victoria and Alfred Docks and adjacent, formerly vibrant, inner-city areas. The present uncertainty and feelings of uprootedness evident among the inshore fishing community will almost certainly be compounded as the V &AW developers and planners edge closer to redeveloping the Silo Precinct which includes the area presently occupied by the inshore fishing industry and community. The challenge facing the V &AW Company is to avoid regressive social engineering by adopting progressive strategies which aim to address both the inshore fishing community's emerging insecurities and (pre)existing topophilic attachments to dockland place.